2020
DOI: 10.1007/s00264-020-04777-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the correction obtained after tibial valgus osteotomy. Comparison of the use of the Hernigou table and the so-called classical method

Abstract: Introduction Medial valgus-producing tibial osteotomy (MVTO) is classicallyusedtotreat earlymedialfemorotibialosteoarthritis. Long-term results depend on the mechanical femorotibial angle (HKA) obtained at the end of the procedure. A correction goal between 3 and 6° valgus is commonly accepted. Several planning methods are described to achieve this goal, but none is superior to the other. Objective The main objective was to compare the accuracy of the correction obtained using either the Hernigou table (HT) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…To date, there has been only one published study considering the imprecision analysis associated with this technique. Nicolau et al [20] have demonstrated greater correction accuracy when using Hernigou tables. This principle relies on the trigonometric calculation based on the length of the osteotomy guide pin.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been only one published study considering the imprecision analysis associated with this technique. Nicolau et al [20] have demonstrated greater correction accuracy when using Hernigou tables. This principle relies on the trigonometric calculation based on the length of the osteotomy guide pin.…”
Section: Introductionmentioning
confidence: 99%